2001
DOI: 10.1074/jbc.m104630200
|View full text |Cite
|
Sign up to set email alerts
|

p75 Co-receptors Regulate Ligand-dependent and Ligand-independent Trk Receptor Activation, in Part by Altering Trk Docking Subdomains

Abstract: Neurotrophins signal via Trk tyrosine kinase receptors and a common receptor called p75. Nerve growth factor is the cognate ligand for TrkA, brain-derived neurotrophic factor for TrkB, and neurotrophin-3 (NT-3) for TrkC. NT-3 also binds TrkA and TrkB as a heterologous ligand. All neurotrophins bind p75, which regulates ligand affinity and Trk signals. Trk extracellular domain has five subdomains: a leucine-rich motif, two cysteinerich clusters, and immunoglobulin-like subdomains IgG-C1 and IgG-C2. The IgG-C1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
122
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 91 publications
(133 citation statements)
references
References 38 publications
9
122
1
1
Order By: Relevance
“…We have confirmed (data not shown) the differential effect of NT-3 and NGF with various receptor constructs (18). In wild type TrkA-expressing cells, 2 nM NGF affords optimal survival.…”
Section: Chimeras Exhibit Trophic Signals In Response Tosupporting
confidence: 68%
See 4 more Smart Citations
“…We have confirmed (data not shown) the differential effect of NT-3 and NGF with various receptor constructs (18). In wild type TrkA-expressing cells, 2 nM NGF affords optimal survival.…”
Section: Chimeras Exhibit Trophic Signals In Response Tosupporting
confidence: 68%
“…Quantitative Western blot analysis (20) with a polyclonal antibody directed to the Trk intracellular domain (203 antisera, a gift of David Kaplan, University of Toronto) indicated that the stable HEK293 4.1 TrkA/B cells express 40,000 -150,000 chimeric receptors/cell (data not shown) (18). All cells were grown in RPMI 1640 supplemented with 5% fetal calf serum, antibiotics, and glutamine.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations